The case of Rios Montt for genocide and cultural development of terror among the Q’eqchi ‘of Guatemala - Flores, Carlos Y. (2017)
This article seeks to connect the construction of a memorial to war victims in the Maya-Q’eqchi’ community of Sahakok, in Alta Verapaz, Guatemala, some 20 years ago with persistent disputes over historical memory and their relationship with the legal prosecution of perpetrators of the violence – in particular the case of genocide charges against former general Efraín Ríos Mont. First, it examines responses to state violence and ways in which the counterinsurgent war affected the perceptions and identities of Maya-Q’eqchi’ during this period. The social implications of state violence are explored, emphasizing what has been referred to as «the cultural elaboration of terror»; this arose when the region’s communities were left without stable symbolic points of reference or adequate cultural mecha-nisms to confront the terrible experiences that occurred in their communities as part of sustained and systematic campaign of military violence. The second part of the article focuses on a process of social and cultural reconstruction in the same region, centered on the community of Sahakok involving the construction of a huge cross some 15 meters high where the names of 916 local victims were inscribed. It analyzes processes of social re-elaboration after the time of nim rahilal (the great suffering), where the survivors, with the aid of external agents, elaborated counter-narratives which came to challenge official discourses about the events they had lived through. The readoption and reelaboration of foundational myths and ritual practices were essential for these processes of physical and cultural recovery, allowing for the recreation of an organized symbolic universe and a moral normative order that has enabled the Maya Q’eqchi’ to struggle against the sociocultural dismemberment that they experienced.